How far along are local energy markets in the DACH+ region? A comparative market engineering approach - Weinhardt, Christof; Mengelkamp, Esther; Cramer, Wilhelm; Hambridge, Sarah; Hobert, Alexander; Kremers, Enrique; Otter, Wolfgang; Pinson, Pierre; Tiefenbeck, Verena; Zade, Michel (2019 ACM e-Energy Workshop on Market Engineering (2019 e-Energy EME Workshop), 2019)
Local energy markets (LEMs) allow localized energy trading between actors within a community. Academic research has actively investigated the LEM concept to support the European energy transition since the turn of the millennium. However, the actual implementation of LEMs in real-life projects has only begun in 2016. We provide a market engineering comparison of the currently most developed LEM projects in the DACH+ region, analyzing and comparing nine LEM implementation projects. So far, LEM projects are in the early stages of development, e. g. proof-of-concept stage, and focus on electricity trading between few residential participants. Regulatory obstacles are evident in all project